ANALISIS KETERAMPILAN PASSING BAWAH BOLA VOLI PADA SISWA KELAS X1 AGRIBISNIS TERNAK RUMINANSIA SMK NEGERI 1 BAWEN - Azwan, Muhamad; Ratimiasih, Yulia; Prastiwi, Bertika Kusuma (Journal of Physical Activity and Sports (JPAS), 2024)
This study aims to analyze the underhand passing skills in volleyball among 11th-grade students of the Agribusiness of Ruminant Livestock class at SMK Negeri 1 Bawen, as many students still struggle to perform accurate ball passes during underhand passing to their teammates. The research employs a quantitative approach using a survey method and an instrument like a volleyball underhand passing assessment rubric. The research sample consists of all 34 students in the 11th grade. Data were analyzed descriptively and presented in percentages. The study results indicate that the majority of students (88%) fall into the "Poor" category with scores ranging from 6 to 8, while 9% are in the "Fair" category with scores between 9 and 11, and 3% are in the "Very Poor" category with scores below 5. None of the students achieved the "Good" or "Very Good" categories. The variation among students is relatively low, with a standard deviation of 1.263, although there is a significant difference between the lowest score (5) and the highest score (11). This study demonstrates that students' underhand passing skills tend to fall within the low to moderate range, with the majority requiring significant improvement. The findings highlight the need for innovative teaching methods and focused training to enhance students' overall underhand passing abilities.